2015
DOI: 10.1371/journal.pone.0115860
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Acute High-Intensity Exercise on Circulating Endothelial Microparticles and Insulin Resistance between Overweight/Obese Males and Females

Abstract: BackgroundAn acute bout of exercise can improve endothelial function and insulin sensitivity when measured on the day following exercise. Our aim was to compare acute high-intensity continuous exercise (HICE) to high-intensity interval exercise (HIIE) on circulating endothelial microparticles (EMPs) and insulin sensitivity in overweight/obese men and women.MethodsInactive males (BMI = 30 ± 3, 25 ± 6 yr, n = 6) and females (BMI = 28 ± 2, 21 ± 3 yr, n = 7) participated in three experimental trials in a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 61 publications
2
45
4
1
Order By: Relevance
“…Some recent studies have begun to examine these issues, although the sex differences remain unclear with some studies reporting lower and others higher resting levels of CD62E+ MPs in sedentary younger women compared with men (Durrer et al , 2015; Gustafson et al , 2015). In addition, some studies are beginning to explore MP responses to an acute bout of aerobic exercise and find differential responses between men and women in CD62E+ (Durrer et al , 2015; Lansford et al , 2016; Shill et al , 2018) and CD34+ MPs (Lansford et al , 2016), suggesting sex differences in responses to vascular stressors with exercise. Thus, future studies specifically designed to examine mechanisms related to sex differences in various populations and in response to an exercise or nutritional intervention might provide better indication as to the use of MPs as sex-specific biomarkers of CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have begun to examine these issues, although the sex differences remain unclear with some studies reporting lower and others higher resting levels of CD62E+ MPs in sedentary younger women compared with men (Durrer et al , 2015; Gustafson et al , 2015). In addition, some studies are beginning to explore MP responses to an acute bout of aerobic exercise and find differential responses between men and women in CD62E+ (Durrer et al , 2015; Lansford et al , 2016; Shill et al , 2018) and CD34+ MPs (Lansford et al , 2016), suggesting sex differences in responses to vascular stressors with exercise. Thus, future studies specifically designed to examine mechanisms related to sex differences in various populations and in response to an exercise or nutritional intervention might provide better indication as to the use of MPs as sex-specific biomarkers of CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Microparticle isolation and identification was based on accepted methodology, as described by Jenkins et al (2013) and Durrer et al (2015). After 15 min of supine rest, a baseline blood sample was collected from the radial artery.…”
Section: Methodsmentioning
confidence: 99%
“…Durrer et al [92] took blood 18 h after high-intensity exercise and found an increase in endothelial MVs. However, intriguingly, this was only evident in females, with a decrease in endothelial MVs in males [92].…”
Section: Exercise and Cardiovascular Stressmentioning
confidence: 99%
“…Durrer et al [92] took blood 18 h after high-intensity exercise and found an increase in endothelial MVs. However, intriguingly, this was only evident in females, with a decrease in endothelial MVs in males [92]. Interestingly, the interpretation of levels may be further complicated by the pre-existing fitness of individuals taking part in studies as a 5-day reduction in daily exercise in normally active young men leads to increased CD31 + CD42b − (apoptotic), but not CD62E + (activated), endothelial-cell-derived MVs [93].…”
Section: Exercise and Cardiovascular Stressmentioning
confidence: 99%